2014
DOI: 10.1039/c3mb70417c
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the Wnt responsive proteome in human cells reveals diverse and cell-type specific networks

Abstract: Wnt signalling is a fundamentally important signalling pathway that regulates many aspects of metazoan development and is frequently dysregulated in cancer. Although many of the core components of the Wnt signalling pathway, such as β-catenin, have been extensively studied, the broad systems level responses of the mammalian cell to Wnt signalling are less well understood. In addition, the cell- or tissue-specific protein networks that modulate Wnt signalling in the diverse tissues or developmental stages in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
(76 reference statements)
1
17
0
Order By: Relevance
“…We chose HEK293T, HeLa, and COS-7 cells for: ( 1 ) Relatively high levels of ectopic expression in these cells allow a large number of constructs to be studied using reporter assays and qRT-PCR. ( 2 ) Regulation of AR and Wnt is reportedly quite different between various lines (Song, et al, 2014). ( 3 ) We validated that: ( a ) β-catenin N-terminus (including introns) is frequently mutated in cancer cells, and ( b ) the N-terminus, and a large portion of the WD40-repeats within β-TrCP1, were intact, by sequencing the genomic DNA of each line (Table S3–S4).…”
Section: Resultsmentioning
confidence: 99%
“…We chose HEK293T, HeLa, and COS-7 cells for: ( 1 ) Relatively high levels of ectopic expression in these cells allow a large number of constructs to be studied using reporter assays and qRT-PCR. ( 2 ) Regulation of AR and Wnt is reportedly quite different between various lines (Song, et al, 2014). ( 3 ) We validated that: ( a ) β-catenin N-terminus (including introns) is frequently mutated in cancer cells, and ( b ) the N-terminus, and a large portion of the WD40-repeats within β-TrCP1, were intact, by sequencing the genomic DNA of each line (Table S3–S4).…”
Section: Resultsmentioning
confidence: 99%
“…We previously performed a large-scale proteomics study to map the Wnt-responsive proteome (17). Proteins were identified whose expression levels responded to exogenous Wnt3A stimulation and we observed that Dnmt1 protein levels exhibited a robust response to Wnt activation in HEK293T cells and in the colorectal cancer cell-lines, RKO and HCT116.…”
Section: Resultsmentioning
confidence: 99%
“…Human Embryonic Kidney cell line HEK293T was maintained in DMEM media (Life Technologies, 11965-092, Carlsbad, CA) containing 10% fetal bovine serum and 1% streptomycin-penicillin under the same conditions. For Wnt activation, media were removed and the cells were washed twice with serum-free McCoy5A media, and 1ml serum-free McCoy5A media, added in each well of 6-well cell culture plate with purified Wnt3a protein (R&D Systems, Inc. 5036- WNP-010/CF, Minneapolis, MN) at the required final concentration of 30ng/ml (17) and the cells were cultured for an additional 0.5, 1, 2, 3, 6, 12, or 24 hours before harvesting. Cells were harvested by scraping the cells off plates and then washed with cold PBS twice for immediate use or storage (-80°C).…”
Section: Methodsmentioning
confidence: 99%
“…However, the prevalence of these mutations seems to be cell-type specific [48,49] . Moreover, a number of recently published studies exploring gene mutations in gastric cancer using high-throughput methodologies (Nextgeneration sequencing and genotyping array) have confirmed CTNNB1 (the gene that encodes b-catenin protein) and APC as driver genes.…”
mentioning
confidence: 99%